2021
DOI: 10.3389/fpsyt.2021.671151
|View full text |Cite
|
Sign up to set email alerts
|

L-Carnitine and Acetyl-L-Carnitine: Potential Novel Biomarkers for Major Depressive Disorder

Abstract: The lack of biomarkers greatly limits the diagnosis and treatment of major depressive disorder (MDD). Endogenous L-carnitine (LC) and its derivative acetyl-L-carnitine (ALC) play antidepressant roles by improving brain energy metabolism, regulating neurotransmitters and neural plasticity. The levels of ALC in people and rodents with depression are significantly reduced. It is necessary to determine whether serum LC and ALC might be used as novel biomarkers for the diagnosis of MDD. Here, ultra-high performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Depression and decreased levels of acetylcarnitine were also found in humans (3). In addition to the results of this study, a decrease in the level of endogenous acetylcarnitine confirmed in several studies can be an objective indicator of depression, and the antidepressant effect of acetylcarnitine supplementation has also been reported (5). In a recent study, acetylcarnitine was identified as a differential metabolite through the comparison of plasma metabolite profiling of the MDD and control groups using a metabolomic approach to identify MDD diagnostic biomarkers (27).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Depression and decreased levels of acetylcarnitine were also found in humans (3). In addition to the results of this study, a decrease in the level of endogenous acetylcarnitine confirmed in several studies can be an objective indicator of depression, and the antidepressant effect of acetylcarnitine supplementation has also been reported (5). In a recent study, acetylcarnitine was identified as a differential metabolite through the comparison of plasma metabolite profiling of the MDD and control groups using a metabolomic approach to identify MDD diagnostic biomarkers (27).…”
Section: Discussionsupporting
confidence: 86%
“…To date, there is no test that can reliably diagnose MDD, and tests such as the Hamilton Rating Scale for Depression (HAMD) and Beck Depression Inventory (BDI) based on subjective interviews with clinicians and patients have been performed for reference ( 4 ). The lack of pathophysiology-based biomarkers for MDD limits its accurate diagnosis and treatment ( 5 ). Biomarkers based on biomolecular mechanisms that can be used for MDD diagnosis, prognosis, and treatment would be useful in providing an objective method for diagnosing MDD rather than a diagnostic method based on subjective evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the acylcarnitine levels of MDD patients changed significantly after treatment. For MDD patients after 2 weeks treatment, LC and LAC levels in the effective treatment group increased significantly, but no significant changes were seen in the ineffective treatment group ( 36 ). After 8 weeks of citalopram or escitalopram treatment in MDD patients, the levels of three short-chain acylcarnitines (C3:0, C4:0, and C5:0) increased, and the medium-chain and long-chain acylcarnitines (C8:0, C10:0, C12:0, C14:2, C16:0, C16:1, C18:0, C18:1, and C18:2) decreased ( 37 ).…”
Section: Carnitine and Depressionmentioning
confidence: 99%
“…Frontiers in Nutrition | www.frontiersin.org ineffective treatment group (36). After 8 weeks of citalopram or escitalopram treatment in MDD patients, the levels of three short-chain acylcarnitines (C3:0, C4:0, and C5:0) increased, and the medium-chain and long-chain acylcarnitines (C8:0, C10:0, C12:0, C14:2, C16:0, C16:1, C18:0, C18:1, and C18:2) decreased (37).…”
Section: Sucrose Consumptionmentioning
confidence: 99%
“…[9] e function of carnitine as a transmitter of fatty acids through the inner membrane of the mitochondria for use in the process of oxidation, facilitating the reabsorption of acetyl CoA, increasing the production of acetylcholine, increasing the production of phospholipids in cell membrane, and preventing the death of neural cells is some of the proposed mechanisms. [9][10][11][12] Although some evidence reported the role of L-carnitine as a safe and effective treatment for depressive disorders, the results of different studies are not the same. [13] is research was conducted to explore the effectiveness of L-carnitine as a complementary medication in the treatment of depression.…”
mentioning
confidence: 99%